2021
DOI: 10.1002/jnr.24808
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and astrocytes show limited, acute alterations in morphology and protein expression following a single developmental alcohol exposure

Abstract: Prenatal alcohol exposure can lead to a wide range of cognitive, behavioral, and physical impairments, collectively described as fetal alcohol spectrum disorders (FASD) (Williams et al., 2015). FASD is the most common cause of nonheritable, preventable mental disability (Williams et al., 2015), yet because the underlying mechanisms causing FASD are not fully established, there is currently no known

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…This is in part due to a lack of understanding of the molecular mechanisms that underlie the widespread symptoms seen in patients. Previous studies have shown that microglia in the somatosensory cortex are sensitive to even a single binge‐level EtOH exposure during the BGS (Ahlers et al., 2015; Lowery et al., 2021). Here, we wanted to determine if a more prolonged BGS exposure could alter microglial dynamics in the long‐term, changing their ability to interact with dendrites and thereby impacting the stability and remodeling of dendritic spines, which have been shown to be a target for EtOH in development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in part due to a lack of understanding of the molecular mechanisms that underlie the widespread symptoms seen in patients. Previous studies have shown that microglia in the somatosensory cortex are sensitive to even a single binge‐level EtOH exposure during the BGS (Ahlers et al., 2015; Lowery et al., 2021). Here, we wanted to determine if a more prolonged BGS exposure could alter microglial dynamics in the long‐term, changing their ability to interact with dendrites and thereby impacting the stability and remodeling of dendritic spines, which have been shown to be a target for EtOH in development.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that EtOH could affect synaptic plasticity through nonmicroglial pathways, despite the known roles of microglia in sculpting neuronal networks in development and adulthood. Additionally, we have recently described changes in microglial morphology in the somatosensory cortex after even a single dose of EtOH during the BGS (Lowery et al, 2021). However, we had not tried to image the physical interactions that microglia make with dendritic spines, allowing the possibility that although microglial dynamics were not altered on a gross level, the targeted recruitment of microglia to dendritic spines may have been disrupted, resulting in changes in synaptic remodeling.…”
Section: 3mentioning
confidence: 99%
“…Confocal z-stacks were collected with a 40× objective and z-step of 0.3 μm to examine microglia arbor complexity for each section with Sholl analysis as described in [ 34 , 37 , 38 ]. Microglia were excluded if their entire process arbor was not contained in the XY-axes or their entire cell body was not contained in the Z-axis.…”
Section: Methodsmentioning
confidence: 99%
“…Foetal alcohol syndrome (FAS) is one of the most severe types of FASD [ 2 ]. Many aspects of FASD disorder have been successfully summarised in vitro and in vivo, including morphological and behavioural defects, but the pathogenesis of the disease is still unclear [ 3 , 4 ]. The unawareness of pregnancy or addictive alcoholism in women during pregnancy has led to FASD in recent years.…”
Section: Introductionmentioning
confidence: 99%